(untitled) (Research, Society and Development, 2023)
Currently, cosmetic dentistry has been growing over the last few years as it has become an area that has conquered a large part of the population and obtained this praise through social media. Thus, appearance becomes a determinant of self-esteem, and aesthetics are sought after for several reasons, including good looks, health, social acceptance and well-being. The objective of this study is to present the techniques and indications for the realization of dental veneers, materials used, advantages and disadvantages, clarifying the steps and post installation maintenance, aiming at rehabilitation for the construction of a smile considered ideal. This work was carried out from February to June 2023 based on specific articles in the area using the following database: US National Library of Medicine/National Institutes of Health (PubMed); Scientific Electronic Library Online (SCIELO) and Google Scholar (Google Scholar). Direct composite resin veneers consist of covering the buccal surface, leaving the dentist to master all the techniques and analyze their correct indication to the patient so that the treatment is carried out individually. This approach becomes a less invasive procedure because it does not require prior preparation, unless the tooth needs reanatomization adjustments. In addition, this technique allows the procedure to be completed in a single session at an excellent cost-benefit ratio, providing the patient with a smile in harmony with function, phonetics and aesthetics.